Cosmological viability of a double field unified model from warm inflation - Rocco D'Agostino; Orlando Luongo (Physics Letters B, 2022)
In this paper, we investigate the cosmological viability of a double scalar field model motivated by warm inflation. To this end, we first set up the theoretical framework in which dark energy, dark matter and inflation are accounted for in a triple unification scheme. We then compute the overall dynamics of the model, analyzing the physical role of coupling parameters. Focussing on the late-time evolution, we test the model against current data. Specifically, using the low-redshift Pantheon Supernovae Ia and Hubble cosmic chronometers measurements, we perform a Bayesian analysis through the Monte Carlo Markov Chains method of integration on the free parameters of the model. We find that the mean values of the free parameters constrained by observations lie within suitable theoretical ranges, and the evolution of the scalar fields provides a good resemblance to the features of the dark sector of the universe. Such behaviour is confirmed by the outcomes of widely adopted selection criteria, suggesting a statistical evidence comparable to that of the standard ΛCDM cosmology. We finally discuss the presence of large uncertainties over the free parameters of the model and we debate about fine-tuning issues related to the coupling constants.